Choosing Wisely Africa: Insights from the front lines of clinical care. (September 2022) - Rubagumya, Fidel; Makori, Kevin; Borges, Hirondina; Mwanzi, Sitna; Karim, Safiya; Msadabwe, Citonje; Dharsee, Nazima; Mutebi, Miriam; Hopman, Wilma M.; Vanderpuye, Verna; Ka, Sidy; Ndlovu, Ntokozo; et al.
Abstract: Background: A multidisciplinary Task Force of African oncologists and patient representatives published the Choosing Wisely Africa (CWA) recommendations in 2020. These top 10 recommendations identify low-value, unnecessary, or harmful practices that are frequently used in Sub-Saharan Africa (SSA). In this study, we describe agreement and concordance with the recommendations from front-line oncologists across SSA. Methods: An electronic survey was distributed to members of the African Organization for Research & Training in Cancer (AORTIC) and oncology groups within SSA using a hierarchical snowball method; each primary contact distributed the survey through their personal networks. The survey captured information about awareness of the CWA list, agreement with recommendations, and concordance with clinical practice. Descriptive statistics were used to summarize study results. Results: 52 individuals responded to the survey; 64% (33/52) were female and 58% (30/52) were clinical oncologists. Respondents represented 15 countries in SSA; 69% (36/52) practiced exclusively in the public system. Only 46% (24/52) were aware of the CWA list and 89% (46/52) agreed it would be helpful if the list was displayed in their clinic. There was generally a high agreement with the recommendations (range 84–98%); the highest agreement was related to staging/defining treatment intent (98%). The proportion of oncologists who implemented these recommendations in routine practice was somewhat lower (range 68–100%). Lowest rates of concordance related to: the use of shorter schedules of radiotherapy (67%); discussion of active surveillance forlow-risk prostate cancer (67%); only performing breast surgery for a mass that was proven to be malignant (70%); and seeking multidisciplinary input for curative intent treatment plans (73%). Conclusion: While most frontline SSA oncologists agree with CWA recommendations, efforts are needed to disseminate the list. Agreement with the recommendations is high but there are gaps in implementation in routine practice. Further work is needed to understand the barriers and enablers of implementation. Highlights: It is imperative that Choosing Wisely Africa (CWA) awareness initiatives are encouraged and spread across Africa. Publication of CWA Oncology in itself will not change the current practice. Clinicians and policy-makers need to promote evidence-based initiatives such as CWA encourage high-value care. CWA implementation will lead to better health outcomes and better stewardship of available health system resources. Most oncologists agree with the current CWA recommendations and would implement them.